Metabolite profiling and functional properties of Curcuma xanthorrhiza kombucha: pH, acidity, antioxidant activity, and LC–HRMS analysis - Nisak, Yunita Khilyatun; Fauziah, Shaddiqah Munawaroh; Rohmawati, Uun; Sutama, Daning Kinanti; Afgani, Chairul Anam; Rahmawati, Fadhilah; Mukhliso, Ida (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Kombucha is a fermented beverage produced through the interaction of yeasts and bacteria, and the addition of medicinal plants may enhance its functional properties. This study investigated the effect of Curcuma xanthorrhiza extract on the physicochemical characteristics, antioxidant activity, and metabolite profile of kombucha. Beverages were prepared with extract concentrations of 0.4–2% (w/v) and compared to black tea kombucha as a control, then fermented for 12 days. The results showed that pH decreased from 4.26 ± 0.16 to 2.13 ± 0.22, while titratable acidity increased from 1.10 ± 0.10% to 5.33 ± 0.15%, indicating active microbial metabolism and organic acid production. Antioxidant activity improved markedly, with IC₅₀ values reduced from 11.9 mg/mL at day 0 to 0.18 mg/mL after fermentation in the control, and from 4.54 mg/mL to 0.61–0.94 mg/mL in Curcuma treatments. Metabolite profiling by liquid chromatography–high resolution mass spectrometry detected more than 40 bioactive compounds, including gluconic acid, citric acid, ferulic acid, vanillic acid, flavonoids, and curcumin derivatives unique to Curcuma kombucha. These findings suggest that Curcuma xanthorrhiza kombucha possesses enhanced antioxidant properties and a diverse metabolite profile, supporting its potential as a functional beverage for health promotion.